TRANSLATION METHODS APPLIED IN THE INDONESIAN TRANSLATION OF THE CHILDREN STORYBOOK “DANNY THE CHAMPION OF THE WORLD” BY ROALD DAHL - BARIROH, AINI ALFIYATUL (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Translation, Translation methods, Children storybook “Danny the Champion of the World”. Translation has an important role to transfer the meaning from one language into another language. To produce a good translation, a translator must use suitable methods in translating a text, whether it is written or spoken text. Children storybookis one of the written texts which has an interesting story with illustrations and picturesthat can enhance the imagination of children. This study is meant to find out the translation methods applied in the Indonesian translation of the children storybook“Danny the Champion of the World” by using Newmark’s theory (1988). This study used document analysis of qualitative approach because the data are from the written material. The data are every first paragraph of every chapter which are 22 chapters in the English and Indonesian translations of the children storybook “Danny the Champion of the World”.  The writer found six translation methods which are used by the translator. The result shows that one sentence uses word-for-word translation, twelve sentences use faithful translation, thirty three sentences use semantic translation, eleven sentences use free translation, three sentences use idiomatic translation, and eleven sentences use communicative translation. The translation method which is mostly used by the translator is semantic translation. Semantic translation is very appropriate to be usedbecause the result of translation is very acceptable and comprehensible to the  readers. Since the readers are mostly children, it is important to make them understand the text easily. The writer suggests that the next researchers, who want to use children storybook “Danny the Champion of the World” as their object, use other parts of the storybook as the data which consists of the dialogs between the characters, in order that an analysis of translation method of the whole storybook can be completed.